STUDI MANAJEMEN PERUBAHAN ORGANISASI POST-TRANSFORMASI PT ASKES (PERSERO) MENJADI BPJS KESEHATAN PADA KCU SEMARANG - Riyan Aprilatama; Anneke Suparwati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2015)
Transformation of PT Askes (Persero) become BPJS Kesehatan in Indonesia was certainty of The Republic Indonesia Act Number 24 2011 about the Indonesia institution of social security (known on Bahasa as Badan Penyelenggara Jaminan Sosial). The transformation made up to branch office changes which were structure, strategy, human resource and system of information.The research aimed to describe and analyze the change management there at Semarang branch office of Indonesia BPJS Kesehatan. This research used qualitative method, and in-depth interview and observation for data collecting method. Respondents, or the subject of the research were the Head and Staffs of Primary Health Care Management Unit.The result of the research showed that the structure changes are the nomenclature of units and anew unit adding. Strategy changes are the promotion intensificating, outsourcing adding, and the orderly premium administration. The change of human resource is the number adding. While the changes of system of information icludes the change of software and the launch of P-Care application.The change management there done by three steps. First, the preparation step. Second the transition and the last continuing step. The change management has been succed enough because of coersif-power approach that the Government and the central office of BPJS Kesehatan mostly contributed by the rules needed.